Market Separations for BOP Producers: The Case of Market Development for the Chanderi Cluster Weavers in India. (October 2015) - Singh, Ramendra; Agarwal, Sharad; Modi, Pratik
In this article, we study the Chanderi handloom cluster as a case of market development by applying and extending Bartels' (1968) theory of market separations. We conduct 12 in-depth semi-structured interviews of various stakeholders involved in the process of market development and validate four market separations suggested by Bartels. Additionally, we also find evidence of a new (fifth) market separation, which we label as 'social market separation'. We empirically argue that social separation is an equally important market separation that inhibits market development at the Bottom of Pyramid (BOP), often acting as a barrier to market development. It may manifest in various forms such as overbearing social customs and regressive socio-cultural practices that may adversely impact the BOP producers' capacity to produce or reduce their access to the markets. The implications of our study for development organizations as well as for marketers include recognizing the importance of conducting market linkages programmes for BOP producers by efficient reduction of five market separations to accelerate market development at BOP, leading to developmental gains.